Prevalence and risk factors of urethral, penile, and scrotal cancers in Iranian men during 2004-2015: A national cancer registry-based study - Allameh, Farzad; Moradi, Afshin; Eslami, Mohammad Javad; Hajian, Mohammad Reza; Hojjati, Seyyed Ali; Faraji, Saba; Akbari, Mohammad Esmaeil (Archives of Men's Health, 2022)
Introduction: Urethral, penile, and scrotal cancers are rare and represent less than 1% of all malignancies. However, they are associated with a high mortality rate and have a significant effect on patients’ quality of life. Penile and urethral cancers comprise 0.6% of all urological cancers. Because of ethnic, geographical, and cultural diversity, risk factors and cancer patterns vary in different communities. We aimed to provide valid information on the prevalence, incidence, and epidemiology of urethral, penile, and scrotal cancers using the National Registry on Cancer of Iran. Methods: This retrospective study of 465 patients included all known cases of urethral, penile, and scrotal cancers from the Department of National Registry on Cancer at the Ministry of Health and Medical Education in Iran during 2004-2015. This study examined the demographic characteristics of patients and discussed the risk factors and possible causes of the above-mentioned cancers. Results: The mean ±SD age at the time of registration was 58.49±20.82 years. The highest and lowest proportions of cases belonged to Tehran/Alborz (14.2%) and Mazandaran (0.65%) provinces, Iran, respectively. Regarding the distribution of records according to a year of registration, these cancers were more prevalent in 2014, and less prevalent in 2004. Conclusion: Urethral, penile, and scrotal cancers were more common in Tehran and Alborz. There was a strong possibility that the prevalence of these cancers is linked to the industrial nature of Tehran and Alborz and the prevalence of human papillomavirus.